UNIT 20D.1 Isolation, Culture and Cryopreservation of Sarcocystis species. Issue 1 (16th May 2017) - Verma, S. K.; Lindsay, D. S.; Grigg, M. E.; Dubey, J. P.
Abstract : More than 200 valid Sarcocystis species have been described in the parasitological literature. The developmental life cycle in the intermediate host and definitive host has only been described for a few species. Sarcocystis parasites are common pathogens infecting a wide range of animals, including humans, and this unit reviews the methods used for isolating infective stages of the parasite from both definitive and intermediate host(s), as well as methods used to initiate cultures from sporocysts and merozoites and for cryopreservation of various Sarcocystis spp. These methods are based on published reports and our experience with Sarcocystis species in cell culture over many years. The information presented is suitable for the efficient culture of many Sarcocystis species; however, some minor modifications may be needed based on the unique developmental patterns of some species. © 2017 by John Wiley & Sons, Inc.